1999
DOI: 10.1021/la970039q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Discharge Gases on Microwave Plasma Reactions of Imidazole on Poly(dimethylsiloxane) Surfaces:  Quantitative ATR FT-IR Spectroscopic Analysis

Abstract: Although our recent studies revealed that under Ar microwave plasma conditions reactions of imidazole with poly(dimethylsiloxane) (PDMS) result in the formation of Si−CH2−imidazole species, the issue of the discharge gas effect on microwave plasma reactions remain unanswered. This study examines how these reactions in the presence of Ar, O2, and CO2 gases under microwave plasma conditions will affect surface reactions on PDMS in the presence of imidazole vapors. When Ar microwave plasma reaction conditions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…It is known that hydrophobicity recovery can be observed for PDMS substrates that have been modified under irradiation with UV/O 3 in a time interval of 2 h. The recovery was explained as being due to the diffusion of nonoxidized low-molar-mass PDMS through cracks in the silica-like surface layer. Toth et al studied silicone rubber surfaces exposed to radio-frequency (rf) plasma or corona discharges in air. They found that silica-like layers formed on the surface, with a thickness of less than 3 nm, using angle-resolved XPS.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that hydrophobicity recovery can be observed for PDMS substrates that have been modified under irradiation with UV/O 3 in a time interval of 2 h. The recovery was explained as being due to the diffusion of nonoxidized low-molar-mass PDMS through cracks in the silica-like surface layer. Toth et al studied silicone rubber surfaces exposed to radio-frequency (rf) plasma or corona discharges in air. They found that silica-like layers formed on the surface, with a thickness of less than 3 nm, using angle-resolved XPS.…”
Section: Resultsmentioning
confidence: 99%
“…25 Variable angle ATR was employed to determine the volume concentration of newly formed species after each step of the reaction as a function of depth by using Ge (50 Â 20 Â 3 mm) crystals and angles varying from 35°to 60°. Since quantitative ATR-FTIR depth profiling requires knowledge of the extinction coefficient for each of these bands, 26 various concentration standards of heparin were prepared, and plots of the absorbance of the 1620 cm À1 OH bending bands as a function of concentration were generated. The extinction coefficients of the bands due to HP is 6778.6 L/mol-cm, whereas the 1710 cm À1 extinction coefficient of CdO vibrations of COOH groups and 1080 cm À1 of CÀOÀC of PEG were previously determined to be 544.32, and 778.58 L/(mol cm), 27 respectively.…”
Section: ' Experimental Sectionmentioning
confidence: 99%
“…The extinction coefficients of the bands due to HP is 6778.6 L/mol-cm, whereas the 1710 cm À1 extinction coefficient of CdO vibrations of COOH groups and 1080 cm À1 of CÀOÀC of PEG were previously determined to be 544.32, and 778.58 L/(mol cm), 27 respectively. Using a double KramersÀKronig transformation (KKT) and previously developed algorithm for quantitative analysis using ATR-FTIR spectroscopy, 26 concentration levels of COOH groups resulting from the microwave plasma modifications, PEG reactions, and HP attachment were determined.…”
Section: ' Experimental Sectionmentioning
confidence: 99%
“…[48] This is attributed to the condensation of neighboring ÀSiÀ(OMe) 3 groups. According to the literature, [48][49][50] stretching vibrations of C=C and C=N cause the peaks at ñ = 1600 and 1564 cm À1 , respectively. …”
mentioning
confidence: 95%